2006
DOI: 10.1002/path.2087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by array CGH of genomic changes associated with the progression or relapse of Wilms' tumour

Abstract: Despite aggressive salvage regimens, approximately half of all children who suffer a Wilms' tumour recurrence will die of their disease. Although there are increasing data on molecular genetic prognostic factors present in the tumour at diagnosis, there is little information regarding the molecular events that occur with Wilms' tumour progression and relapse. In the present study, microarray-based comparative genomic hybridization (aCGH) analysis has been carried out on 58 Wilms' tumour samples, which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 27 publications
(32 reference statements)
2
43
1
1
Order By: Relevance
“…To date, expression profiling studies have provided inconsistent results, perhaps due to the cellular heterogeneity found in WT, whereas genomic copy number analyses look more promising to discriminate relapsing tumors [20][21][22]. This is consistent with the predictive value of allele loss at chromosomes 1p and 16q found in the large NWTS-5 trial, although the critical genes or pathways remain to be defined [23].…”
Section: Filippo Spreaficosupporting
confidence: 56%
“…To date, expression profiling studies have provided inconsistent results, perhaps due to the cellular heterogeneity found in WT, whereas genomic copy number analyses look more promising to discriminate relapsing tumors [20][21][22]. This is consistent with the predictive value of allele loss at chromosomes 1p and 16q found in the large NWTS-5 trial, although the critical genes or pathways remain to be defined [23].…”
Section: Filippo Spreaficosupporting
confidence: 56%
“…It encompasses five genes, including ING5, a putative tumor suppressor gene that may modulate p53 function (37). The translocation is unbalanced and duplicates a 28-Mb region of distal 15q, a rearrangement that has also been implicated in the pathogenesis of Wilms' tumor (15,38). Thus, although this is one of the three germ-line rearrangements that inspired the study, the partial trisomy 15q likely also contributed to the pathogenesis of Wilms' tumor in this patient and the 2q37 deletion alone may not have been causal.…”
Section: Discussionmentioning
confidence: 92%
“…Identification of other genes involved in the etiology of sporadic Wilms' tumor therefore remains an important priority. Studies of loss of heterozygosity (LOH), loss of imprinting, and constitutional chromosomal defects have implicated several recurrent changes in Wilms' tumor at chromosomes 11p15, 1p, 1q, 7p, 9q, 14q, 16q, and 22 (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Natrajan ve ark. 'nın (14) Wilms tümöründe KGH yöntemi ile genomik değişiklikleri inceledikleri bir çalışmada, Wilms tümöründe kromozomal sapmanın sayısındaki artış ile tümör progresyonu ve relaps arasında ilişki bulunmuştur. Ek olarak spesifik genetik değişiklik 17p kaybının, tümör progresyonuyla bağ-lantılı ve bu anomalinin olasılıkla tümör gelişiminde son basamak olduğu saptanmıştır.…”
Section: Karşılaştırmalı Genomik Hibridizasyon Ve Onkolojik Araştırmaunclassified